Numerical energy and exergy evaluation of a filament bulb controlled convective heat dryer - Ajah, Stephen A.; Ikwuagwu, Chibuzo V.; Ezurike, Benjamin O (Penerbit Universiti Kebangsaan Malaysia, 2022)
The mathematical model for temperature regime thermal analysis evaluation of convective heat dryer has been done. Control volume analysis was adopted in this work while taking note of all the feasible heat transfer mechanisms around the system. Mathematical expressions for the energy, exergy, entropy generation as well as destroyed exergy were derived using the control volume. The consumed energy, exergy, entropy generation and exergy destruction of the dryer were computed. The system temperature gradually increased from its initial room temperature of 270˚C to 720˚C at approximately 2700 secs. The temperature thereafter dropped and stabilized to about 670˚C at 4600 secs while the element dried gradually. The moisture removal curve followed the same trend as that of the temperature with gradual variation from 0.5 to 13.2g/mol. The peak energy from the system is approximately 958J against the useful exergy of 443J which shows that 46.24% of the expended energy was actually useful for the drying purpose and about 10.23% was lost. The energy and exergy efficiencies were also computed and results showed that the efficiencies are functions of temperature just like other influencing parameters which has to be technically controlled. Peak energy efficiency of approximately 54.6% was recorded in the dryer with the peak exergy efficiency of 23.4%. The dryer also yielded a better dried product as compared with the traditional means of drying.